Predictors and Risk Factors of Armed Robbery Victimisation in Nigeria: An Integrated Theoretical Perspective - Reuben, Etuk, Grace; Nnam, Macpherson U. (European Scientific Journal, ESJ, 2018)
The rapidly increasing rate of armed robbery victimisation in Nigeria necessitated the integration of five relevant victimological and sociological/criminological theories in this paper to provide a detailed account of the causal processes and conditions that predict this offending behaviour. The paper is essentially theoretical, relying mainly on library research and review of relevant literature to obtain necessary data and information. It was found that armed robbery, as a social problem, is caused by many factors and the associated risk factors are countless and destructive. Issues raised suggest a policy direction that will ensure a timely and objective incorporation of the global best practices—as enshrined in the Victims’ Bill of Right (VBR), among others, into the Nigerian legal system, so as to effectively combat armed robbery victimisation and related offences. The official introduction of victim impact statements, victim-offender reconciliation, crisis interventions and restorative justice into the Nigerian criminal justice system is also advocated for. Additionally, it is suggested that social service agencies and/or providers should extend their caring services beyond victims of disaster/disease and terrorism to include armed robbery victims, given the alarming nature and extent of this phenomenon in the country.